Aggregation enhanced excimer emission (AEEE) with efficient blue emission based on pyrene dendrimers. Issue 19 (21st April 2016) - Abd-El-Aziz, Alaa S.; Abdelghani, Amani A.; Wagner, Brian D.; Abdelrehim, Elsayed M.
Abstract : A series of fluorescent dendrimers with pyrene moieties exhibited aggregation enhanced excimer emission (AEEE). Increases in the dendrimer generation caused emission at 480 nm with a high excimer/monomer emission intensity ratio. Abstract : Fluorescence dendrimers have been developed, which exhibit aggregation enhanced excimer emission (AEEE). In this article, the synthesis and characterization of three generations of organoiron dendrimers with a flexible core is described. Different photoactive pyrene moieties with and without alkyl chains were used to functionalize the dendritic peripheries. The luminescence properties of these dendrimers were examined in various solvents and concentrations as well as in THF/water mixtures. It was determined that the alkyl chain attached to pyrene moieties had a significant impact on the emission wavelength. Interestingly, dendrimers exhibited weak emission when dissolved in organic solvents but strong emission when aggregated in mixed organic/aqueous solvents. Different emission behaviour was observed in the case of second generation dendrimers, due to the presence of a high number of pyrene moieties. The solution emitted much bluer light relative to the zero and first generations, which emitted around 480 nm. In addition, the change in the distance between two pyrene moieties affects the formation of strong or weak excimers. The excimer–monomer intensity ratios ( I E / I M ) showed the existence of the unique phenomenon of AEEE. The large difference between the aggregated molecules in various THF/water ratios was detected by TEM. Redox activities of the dendrimers were also measured. A single redox wave was displayed in all dendrimers and the intensity of the redox waves increased by increasing the dendrimer generation. All dendrimers possessed good thermal stability and were shown to have two thermal degradation processes.